Microbial Zoopoetics in Octavia Butler’s Clay’s Ark - Magnone, Sophia Booth (Humanimalia, 2016)
This paper reads Octavia Butler’s 1984 novel Clay’s Ark as a speculative handbook for living collaboratively in a more-than-human world. Drawing on Aaron Moe’s theory of zoopoetics, as well as emerging research on the effects of the human microbiome on health, behavior, and personality, I consider how the novel’s “villain,” an infectious microbe, might be not just a germ but an author, writing difference into the text of the human species. Depicting this interspecies relationship as both troubling and productive, Butler suggests the urgent need for humans to construct responsible and mutually beneficial forms of collaboration with their nonhuman neighbors of all sorts.